Differences of onset and duration of judo specialization between male and female 2020 Tokyo Olympic judo athletes - Narazaki, N.; Watanabe, R (Bulletin of University of Teacher Education Fukuoka, 2023)
This study aimed to examine differences of onset and duration of judo specialization between male and female 2020 Tokyo Olympic judo athletes, as well as between judo athletes in the 2020 Tokyo and 2016 Rio de Janeiro Olympic Games. Seven male and seven female Japanese judo athletes participated in the 2020 Tokyo Olympic Games were selected as subjects. Onset and duration of judo specialization were determined for each athlete and compared by sex using independent t-tests. These variables for the 2020 Tokyo Olympic judo athletes were also compared with those for the 2016 Rio de Janeiro Olympic judo athletes determined in our previous study using two-way analyses of variance. The results showed that there were no significant differences on the onset and duration of judo specialization between male and female 2020 Tokyo Olympic judo athletes (onset: 16.6±1.6 years for male vs. 15.4±2.1 years for female, p=0.249; duration: 10.4±2.2 years for male vs. 10.2±2.6 years for female, p=0.905). On the other hand, there showed a significant main effect for sex on the onset of judo specialization in judo athletes of the 2020 Tokyo and 2016 Rio de Janeiro Olympic Games (16.3±1.4 years for male vs. 14.2±0.8 years for female, p<0.05). The present results suggest that female Olympic judo athletes underwent earlier onset and comparable duration of judo specialization compared with male counterparts, which should be paid attention to by coaches to explore optimal individualization of training regimens.